The Fight Against Terrorism and Extremism in ahe Central Asian Countries - Members of the SCO - L. Yu. Gusev (Международная аналитика)
After obtaining independence the republics of Central Asia faced with difficulties of regional security maintenance. The first threat to regional security comes from political instability in the Caucasus, the Xinjiang Uygur Autonomous Region of China, Afghanistan, the Middle and Near East. The second dangerous factor is a terrorist activity in the Central Asia accompanied by growth of various offices and funds of Islamist orientation in the Central Asia. With these factors in mind, the author considers possible methods of combating terrorists in different countries of the Central Asia.